Photochemical Oxidation of o-Toluidine by Fenton Reagent - Kumar, Dharmendra (Asian Journal of Chemistry, 2010)
Photo chemical oxidation of o-toluidine by Fenton reagent was studied. The effect of different reaction parameters such as concentration of substrate, H2O2, FeSO4, pH, polarity of solvent and catalyst variation was studied. The progress of the reaction was observed by TLC. Photoproduct was characterized by physical, chemical and spectral methods. A tentative mechanism has been proposed with overall reaction.